EVALUASI KADAR GLUKOSA DARAH PASIEN DIABETES MELITUS TIPE 2 DENGAN HIPERTENSI DI RUANG CEMPAKA RUMAH SAKIT PANTI WILASA CITARUM SEMARANG - Wisma Supriatining Krestiana; Paulina Maya Octasari (Journal Clinical Pharmacy and Pharmaceutical Science, 2022)
Diabetes mellitus is a degenerative disease that increases every year in the world. The most common case of DM is a case of type 2 DM (90%). Type 2 DM with hypertension is one of the ten biggest diseases in Panti Wilasa Citarum Hospital Semarang. The purpose of this study was to evaluate and calculate the value of decreasing blood glucose levels. The type of research conducted was descriptive observational using a prospective method. The study was conducted in Cempaka Room at Panti Wilasa Citarum Hospital Semarang in the period March-April 2019. The research subjects were patients aged 18-60 years with National Health Insurance who met the inclusion-exclusion criteria who were willing to be respondents in this study. Data is processed and analyzed qualitatively and quantitatively. The results showed that the target blood glucose level of type 2 DM patients with hypertension at Panti Wilasa Citarum Hospital Semarang was achieved. Patients experienced a decrease in GD2JPP and GDP levels in single antidiabetic therapy of 73.68%, two combinations of antidiabetic 95%, three combinations of antidiabetic 100%.